Modification of colorimetric method based digital soil test kit for determination of macronutrients in oil palm plantation - Yamin, Muhammad; Ismail, Wan Ishak bin Wan; Kassim, Muhamad Saufi bin Mohd; Aziz, Samsuzana Binti Abd; Akbar, Farah Naz; Shamshiri, Redmond R.; Ibrahim, Muhammad; Mahns, Benjamin (International Journal of Agricultural and Biological Engineering, 2020)
It is the need of time that oil palm farmers must perform the spatially planned soil analysis to know about the fertilizer sufficient and deficient zones of land. Colorimetric method is a suitable and fast solution of soil analysis for NPK determination using the digital soil test kit. NPK determination procedure with a digital soil test kit was undefined for oil palm. Furthermore, the digital soil test kit determines the passage of light through an opaque medium of soil solution with a specified reagent. Therefore, environmental light may interfere leading to wrong results of NPK measurement. Likewise, this equipment was non-incorporable with the controller of any VRT fertilizer applicator. In this research, these issues were addressed and the NPK measurement procedure was defined for oil palm plantation by modifying the ‘soil to water’ ratio in sample soil solution with an optimum environmental light range of 18-23 W/m2. ‘Soil to water’ ratios were found for nitrogen, phosphorus and potassium as 0.31 to 5.00, 1.00 to 5.00 and 4.50 to 5.00, respectively to fit the requirement of NPK for oil palm in the prescribed range of the equipment. Validation study of modified digital soil test kit showed that 91.7% N, 89.6% P and 93.8% K results of modified digital soil test kit were matched with analytical laboratory method. Thus, the reliability of NPK results using digital soil test kit was enhanced, making the kit incorporable with the controller of variable rate fertilizer applicator through remote monitoring based data acquisition system. The outcome of this research can be used in the development of an IoT network data fusion for dynamic assessment of the NPK variation in the soil and nutrient management in oil palm plantations.Keywords: digital soil test kit, variable rate fertilizer applicator, oil palm, NPK measurement, data acquisition system, colorimetric methodDOI: 10.25165/j.ijabe.20201304.5694Citation: Yamin M, Ismail W I W, Kassim M S M, Aziz S B A, Akbar F N, Shamshiri R R, et al. Modification of colorimetric method based digital soil test kit for determination of macronutrients in oil palm plantation. Int J Agric & Biol Eng, 2020; 13(4): 188–197.